2013
DOI: 10.4103/0973-1482.110380
|View full text |Cite
|
Sign up to set email alerts
|

Primary branchiogenic carcinoma: Report of a case and a review of the literature

Abstract: Branchiogenic carcinoma, which is squamous cell carcinoma arising in a branchial cyst, is extremely rare and a highly contentious clinicopathologic entity. A 56-year-old male presented with a well-defined, fluctuant, painless mass on the right side of the neck which was excised with a diagnosis of branchial cyst. The pathological diagnosis was branchial cleft squamous cell carcinoma, which was characterized microscopically by a branchial cleft cyst with a tumour and a non-tumour transitional zone. The report h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…In order to exclude any primary tumor are recommended a meticulous clinical evaluation of the oral cavity, cervical lymph nodes, and thyroid gland (along with hormonal profile) followed by fibroscopy of the upper aerodigestive tract, magnetic resonance, and PET/CT total body. Some authors suggested to perform bilateral tonsillectomy, Waldeyer's ring biopsy, or random pharyngeal biopsies in patients positive for HPV and EBV, even in absence of macroscopically suspicious lesions resulting from instrumental evaluation 6,7,9 . Since our patient was negative to HPV and EBV and no oro‐rino‐pharyngeal lesions were detected, these procedures were not performed in accordance to other Authors' opinion 10‐12 …”
Section: Discussionmentioning
confidence: 92%
“…In order to exclude any primary tumor are recommended a meticulous clinical evaluation of the oral cavity, cervical lymph nodes, and thyroid gland (along with hormonal profile) followed by fibroscopy of the upper aerodigestive tract, magnetic resonance, and PET/CT total body. Some authors suggested to perform bilateral tonsillectomy, Waldeyer's ring biopsy, or random pharyngeal biopsies in patients positive for HPV and EBV, even in absence of macroscopically suspicious lesions resulting from instrumental evaluation 6,7,9 . Since our patient was negative to HPV and EBV and no oro‐rino‐pharyngeal lesions were detected, these procedures were not performed in accordance to other Authors' opinion 10‐12 …”
Section: Discussionmentioning
confidence: 92%
“…Intracystic hemorrhage can demonstrate hyperintensity on T1 and T2 weighted images, while solidification of cystic fluid displays homogeneous hypo intensity on T2 weighted images without enhancement. Atypical branchial cleft cysts can be difficult to differentiate from cystic malignancies even on MRI, and tissue sampling may be necessary [9]. Definitive treatment is complete surgical excision of the cyst and tract.…”
Section: Discussionmentioning
confidence: 99%
“…Можно отметить, что метастазы ПКР без выявленного первичного очага наиболее характерны для узлов шеи и верхней части туловища, что соответствует данным литературы [7,8]. В паховой области такие случаи выявляются реже.…”
Section: Discussionunclassified
“…Несколько слов скажем об озлокачествленных бранхиогенных кистах. В представленном материале случаев, достоверно относящихся к данной нозологии, мы не обнаружили, поскольку ни одно из наблюдений не удовлетворяло критериям, используемым для спецификации этой нозологии [7]. Отчасти трудности в объективной диагностике были обусловлены или поздними морфогенетическими стадиями процесса, что приводило к стиранию фоновых структур, или же тем обстоятельством, что в ряде случаев проводилась только биопсия, что исключало возможность определить пространственную характеристику процесса.…”
Section: Discussionunclassified